PENGARUH KOMUNITAS DAN KEPADATAN RAYAP TANAH TERHADAP KERUSAKAN RUMAH - Ginuk Sumarni; Agus Ismanto (Jurnal Penelitian Hasil Hutan, 1989)
The  study    was carried   out  at  Cibadak,   Padalarang and Pacet   which  have soil  types  of  Renzina,    litosol  and  brown forest   soil  complex;    Brown   mediteran   complex   and  Brown   Andosol   and  brown  regosol  association,    respectively.    It  is  found   that  the  first  soil  type  has  the  highest   subterranean    termites   density   as  well  as house  damages.Subterranean     termites   species  found   at  the   whole   locations    are  Macrotermes gilvus  (Hagen)    and  Microtermes  insperatus   Kemner.